Neuroprotective Effects of Proanthocyanidins, Natural Flavonoids Derived From Plants, on Rotenone-Induced Oxidative Stress and Apoptotic Cell Death in Human Neuroblastoma SH-SY5Y Cells - Ma, Jian; Gao, Shan-Shan; Yang, Hai-Jie; Wang, Mian; Cheng, Bin-Feng; Feng, Zhi-Wei; Wang, Lei (Frontiers in Neuroscience, 2018)
Proanthocyanidins (PA) are natural flavonoids widely present in many vegetables, fruits, nuts and seeds, and especially in grape seed. In the present study, we examined the neuroprotective effects of PA and the underlying molecular mechanism in rotenone model of Parkinson’s disease (PD). We found that pretreatment with PA significantly reduced rotenone-induced oxidative stress in human neuroblastoma SH-SY5Y dopaminergic cells. In addition, PA markedly enhanced cell viability against rotenone neurotoxicity and considerably blocked rotenone-induced activation of caspase-9, caspase-3, and cleavage of poly (ADP-ribose) polymerase (PARP), biochemical features of apoptosis. Signaling pathway screening revealed that PA suppressed rotenone-induced phosphorylation of p38, JNK, and ERK. Further study demonstrated that the pro-apoptotic effect of rotenone was mediated by p38, JNK, and ERK signaling, and inhibitors of these three signaling pathways reproduced the protective effect of PA separately. In summary, our results demonstrated that PA mitigated rotenone-induced ROS generation and antagonized apoptosis in SH-SY5Y cells by inhibiting p38, JNK, and ERK signaling pathways, and it may provide a new insight of PA in PD therapy.